2013
DOI: 10.1007/s00199-013-0758-y
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization effect of international trade in a perfect foresight dynamic general equilibrium model

Abstract: Abstract:In the present paper, we consider a two-country, two-good, two-factor general equilibrium model with CIES non-linear preferences, asymmetric technologies across countries and decreasing returns to scale. It is shown that aggregate instability and endogenous fluctuations may occur due to international trade. In particular, we prove that the integration into a common market on which countries trade the produced good and the capital input may lead to period-two cycles even when the closed-economy equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that in a perfect foresight model with many consumers, a competitive equilibrium path behaves like an optimal growth path; see Becker (), Bewley (), Yano (), and Epstein (). Building on this property, Nishimura and Yano() and, Nishimura et al ., () have shown that a country's business cycles (i.e., two‐period cycles) can spread throughout the world once trade opens.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in a perfect foresight model with many consumers, a competitive equilibrium path behaves like an optimal growth path; see Becker (), Bewley (), Yano (), and Epstein (). Building on this property, Nishimura and Yano() and, Nishimura et al ., () have shown that a country's business cycles (i.e., two‐period cycles) can spread throughout the world once trade opens.…”
Section: Introductionmentioning
confidence: 99%
“…See, for instance, Nishimura and Shimomura (2002), Nishimura (2014, 2019) and Sim and Ho (2007). 10 When international capital mobility is also introduced the results obtained tend to support the view that trade is destabilizing, as in Nishimura et al (2010Nishimura et al ( , 2014 in a two-good, two-factor model with infinitely-lived agents and Le Riche (2017) 9 Moreover, along these fluctuations we obtain a procyclical behavior of exports generated by the existence of taste for variety and intra-industry trade, in accordance with the pattern exhibited by data for developed economies. See De Bock (2010) and Engel and Wang (2011).…”
Section: Introductionmentioning
confidence: 87%
“…The complementarity between consumption and real money balances under the CIA constraint then leads the households to contemplate a reduction in consumption. Note that, in order for the sunspot belief to be potentially self-fulling it must be the case 1 See, for example, Weder (2001), Lahiri (2001), Nishimura and Shimomura (2002a, b), Velasco (2003, 2004), Aloi and Lloyd-Braga (2010), Hu and Mino (2013), and Nishimura et al (2014). 2 One testable implication of these results is that open economies may be less volatile.…”
Section: Introductionmentioning
confidence: 99%